PWE-267 Urinary TLR4: a novel biomarker to identify patients with acute kidney injury in patients with acute on chronic liver failure. (28th May 2012) - Shah, N; Mohammed, F; Jover-Cobos, M; Macnaughtan, J; Davies, N A; Moreau, R; Paradis, V; Moore, K; Mookerjee, R P; Jalan, R
Abstract : Introduction: Patients with stable cirrhosis often present with acute deterioration of cirrhosis secondary to precipitating illness which may progress to organ failure, a condition referred to as acute on chronic Liver failure (ACLF). A proportion of these patients develop renal dysfunction which do not fulfil criteria for the diagnosis of hepatorenal syndrome (HRS). We hypothesised that the kidneys in patients who develop renal dysfunction in ACLF would exhibit histological and biomarker evidence of acute kidney injury (AKI). Since ACLF is associated with systemic inflammatory response (SIRS) we aimed to look for Toll like receptor (TLR) 4 and 2 which recognise pathogens and when activated lead to apoptosis and production of cytokines. Methods: Study 1 : 74 subjects [healthy volunteers (6), compensated alcoholic cirrhosis (11), acute deterioration of alcoholic cirrhosis (57)] were included prospectively. Urinary biomarkers, kidney injury molecule-1 (KIM-1, a marker of renal injury), Glutathione S-Transferase (πGST, αGST; markers of proximal and distal tubular injury) (Commercial ELISA), and urinary TLR4 (Western Blotting) were measured. Study 2 : Renal biopsies were available from 8 alcoholic cirrhosis patients (3 AKI; 5 HRS) which were stained for TLR4, TLR2 and, Caspase-3. Results: Study 1 : Nine patients developed AKI on the background of acute deterioration of cirrhosis and 3 had HRS. KIM-1, πGST and αGST were higher in patients with acute deterioration of cirrhosis compared with controls but did not differ in those with and without AKI. Urinary TLR4 values were significantly higher in patients with acute deterioration of cirrhosis with AKI (4.7±1.1) compared to controls (0.38±0.04) and stable cirrhosis (0.32±0.08) and patients with acute deterioration of cirrhosis without renal dysfunction (1.6±0.32) (p<0.01) respectively. Conclusion: These data provide evidence for severe tubular injury and apoptosis in patients with AKI and identifies urinary TLR4, as a novel biomarker to identify AKI in Acute deterioration of cirrhosis. Competing interests: None declared.